2006
DOI: 10.1177/154405910608500211
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride Varnish Efficacy in Preventing Early Childhood Caries

Abstract: To determine the efficacy of fluoride varnish (5% NaF, Duraphat ® , Colgate) added to caregiver counseling to prevent early childhood caries, we conducted a two-year randomized, dental-examinermasked clinical trial. Initially, 376 caries-free children, from low-income Chinese or Hispanic San Francisco families, were enrolled (mean age ± standard deviation, 1.8 ± 0.6 yrs). All families received counseling, and children were randomized to the following groups: no fluoride varnish, fluoride varnish once/year, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
221
3
16

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(249 citation statements)
references
References 19 publications
9
221
3
16
Order By: Relevance
“…This finding corroborates those of previous studies (6,10,12,16,18,19). There was a 45.7% reduction in WSL size, which is in agreement with previous studies (9,10,12,16).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding corroborates those of previous studies (6,10,12,16,18,19). There was a 45.7% reduction in WSL size, which is in agreement with previous studies (9,10,12,16).…”
Section: Discussionsupporting
confidence: 93%
“…Fluoride varnishes have gained popularity due to their high concentration and safety during application (8). A number of studies have demonstrated that fluoride varnishes are able to remineralize incipient carious lesions as well as prevent decay when used with other preventive measures, such as diet control and reduction of dental biofilm (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the fact that early childhood caries has been affecting children below three years, the disease is currently considered a public health problem (16)(17)(18)(19) . Its etiology is complex and results from the interaction of several factors, such as: high consumption of fermentable carbohydrates, negligence in oral hygiene, low family socioeconomic status, and mother's limited educational level (20)(21)(22)(23) .…”
Section: Discussionmentioning
confidence: 99%
“…Since it is a public health problem that adversely affects the lives of many children, sometimes as soon as the eruption of primary teeth [11,12], the use of FV has been proposed as a way to prevent [7,13] and control the disease. It is vital that dentists [14] and health care planners know the true benefits that these products can provide to primary dentition [11,15].…”
Section: Introductionmentioning
confidence: 99%
“…It is vital that dentists [14] and health care planners know the true benefits that these products can provide to primary dentition [11,15].…”
Section: Introductionmentioning
confidence: 99%